PENGARUH LAYANAN BIMBINGAN KELOMPOK TEKNIK DESENSITISASI SISTEMATIS TERHADAP KECEMASAN LULUS MATA KULIAH MAHASISWA SEMESTER II BIMBINGAN KONSELING FIP UNIVERSITAS NEGERI MEDAN T.A. 2020/2021 - Rahmulyani Rahmulyani; Nindya Ayu Pristanti; Pawlin Silitonga (Universitas Negeri Medan, 2021)
Abstract: The Effect of Group Guidance Service with Systematic Desensitization Techniques on Anxiety of Passing Course Semester II Guidance and Counseling Students, Faculty of Education, Universitas Negeri Medan Academic Year 2020/2021. The purpose of this study was to determine the effect of group guidance services with systematic desensitization techniques on the anxiety of passing course in the second semester of guidance and counseling students at FIP UNIMED academic year 2020/2021. This study uses a quantitative approach with a quasi-experimental method with one group pre-test and post-test design. Data collection techniques using a questionnaire. The research subjects were 8 people who were selected by screening using an anxiety scale to pass the course. data analysis used Wilcoxon test, The result showed that the group guidance service of the systematic desensitization technique has proven effective in reducing the level of anxiety in passing students' courses, where Jcount > Jtable is 6 > 4, from the crisis table J for the Wilcoxon marked level test for n = 8 , = 0.05. This can also be seen through the results of the calculation with the pre-test score obtained an average of 118.5 while the post-test data obtained an average of 61.5. Keywords: Group Guidance, Systematic Desensitization, Anxiety Passing Courses.